DOES INTEGRATION OF INFORMATION AND COMMUNICATION TECHNOLOGY (ICT) IN A PRIMARY HEALTH CARE CLINIC IMPROVES CLIENT’S SATISFACTION? - Nora’i Mohd Said; Hamzah Abdul Ghani; Farizah Hairi (Malaysian Journal of Public Health Medicine, 2001)
The objective of this study was to find out whether integration of Information and Communication Technology (ICT) in a Primary Health Care Clinic improves client’s waiting time. This was a descriptive study based on a total of 588 clients, i.e. 291 clients from an ICT integrated primary health care clinic, which was Putrajaya Health Clinic and 297 clients from a manual health clinic, which was Salak Health Clinic, from 5th December 2000 until 10th January 2001. Clients attending both clinics during this study period were systematically random sampled. Information was obtained from structured questionnaires. Data were analysed with Statistical Package for Social Sciences (SPSS) version 10.0. Selected quantitative time variables, their mean and standard deviation were calculated. Integration of ICT in a primary health care clinic did not improve client’s waiting time. It was demonstrated by this study that the integration of ICT in Putrajaya Health Clinic led to significantly longer average waiting time (39.76 minutes) and longer average total time spend in the clinic (57.14 minutes) as compared to a manual clinic, Salak Health Clinic where its average waiting time was only 23.13 minutes and average total time spend in the clinic was 39.15 minutes. Based on the findings, it is possible that integration of ICT in a primary health care clinic could not play as a significant factor for improving or reducing client’s waiting time in Putrajaya Health Clinic yet, at least not for the time being. This is the first study to document waiting times specifically in our first ICT integrated primary health care clinic. Since it was found that integration of ICT in a primary health care clinic had made client’s waiting time significantly longer than the waiting time in a manual clinic, it could be interesting for future research to look into client’s satisfaction in an ICT environment clinic.